2021
DOI: 10.1101/2021.02.26.21252512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

REACT-2 Round 5: increasing prevalence of SARS-CoV-2 antibodies demonstrate impact of the second wave and of vaccine roll-out in England

Abstract: Background England has experienced high rates of SARS-CoV-2 infection during the COVID-19 pandemic, affecting in particular minority ethnic groups and more deprived communities. A vaccination programme began in England in December 2020, with priority given to administering the first dose to the largest number of older individuals, healthcare and care home workers. Methods A cross-sectional community survey in England undertaken between 26 January and 8 February 2021 as the fifth round of the REal-time Assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
43
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 20 publications
11
43
2
1
Order By: Relevance
“…The data are also in keeping with community seroprevalence data in blood donors showing a rapid rise in prevalence of spike protein antibody-positive but nucleoprotein-antibody negative adults [12]. Antibody responses in our cohort were significantly higher compared with recent estimates using self-collected LFDs in the vaccinated people in the community, even when compared with LFD results in this analysis, suggesting that this collection method may not be suitable for assessing vaccine responses through home testing for older adults [13]. Further studies are ongoing to assess antibody and cellular responses as well as antibody waning in adults and older adults receiving extendedinterval schedules with any COVID-19 vaccine.…”
Section: Resultssupporting
confidence: 74%
“…The data are also in keeping with community seroprevalence data in blood donors showing a rapid rise in prevalence of spike protein antibody-positive but nucleoprotein-antibody negative adults [12]. Antibody responses in our cohort were significantly higher compared with recent estimates using self-collected LFDs in the vaccinated people in the community, even when compared with LFD results in this analysis, suggesting that this collection method may not be suitable for assessing vaccine responses through home testing for older adults [13]. Further studies are ongoing to assess antibody and cellular responses as well as antibody waning in adults and older adults receiving extendedinterval schedules with any COVID-19 vaccine.…”
Section: Resultssupporting
confidence: 74%
“…We used the UK's national COVID-19 Infection Survey (ISRCTN21086382), which includes a representative sample of households and has longitudinal follow-up, to study population-wide anti-trimeric spike IgG antibody responses after SARS-CoV-2 vaccination by time since vaccination, considering the vaccine type (BNT162b2 or ChAdOx1), the number of doses received, the presence or absence of prior SARS-CoV-2 infection and demographic factors. Our results build on the REACT-2 study, a serial cross-sectional UK study of antibody responses using a binary point-of-care lateral flow assay 12 . Specifically, we investigate longitudinal data in the same individuals with a validated quantitative laboratory antibody assay, which has previously been shown to correlate with neutralizing activity (correlation coefficient of 0.76) 13 , allowing the assay to act as a potential correlate of protection based on the strong association between quantitative neutralizing activity and protection from infection 14 .…”
mentioning
confidence: 85%
“…Nonetheless, in earlier analyses we have shown that participant reports of date of onset of their symptoms produce an epidemic curve that very closely tracks the epidemic. 27,30,31 Respondents were restricted to reporting a single date of (initial) symptom onset which does not allow for delayed onset of some symptoms, nor does it allow for the reporting of relapsing symptoms which appear to be a feature of Long COVID. 6 A further limitation, despite the high response rate for a community surveillance study, is the possibility of participation bias as the REACT-2 study included a home antibody self-test; 27 it is plausible that people with persistent symptoms may have been more likely to participate in order to ascertain their antibody status.…”
Section: Strengths and Limitationsmentioning
confidence: 99%